2009
DOI: 10.1016/j.yfrne.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective actions of androgens on motoneurons

Abstract: Androgens have a variety of protective and therapeutic effects in both the central and peripheral nervous systems. Here we review these effects as they related specifically to spinal and cranial motoneurons. Early in development, androgens are critical for the formation of important neuromuscular sex differences, decreasing the magnitude of normally occurring cell death in select motoneuron populations. Throughout the lifespan, androgens also protect against motoneuron death caused by axonal injury. Surviving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 159 publications
3
48
0
Order By: Relevance
“…Thus, the results reported here suggest protective effects after DHT treatment on chronic EAE, proposing a therapeutic potential for this neuroactive steroid. Previous observations obtained in other experimental models of neurodegeneration described protective [40][41][42][43] or detrimental effects after DHT treatment [44,45] . Moreover, controversial results were also reported in models of MS [16][17][18]23] .…”
Section: Discussionmentioning
confidence: 72%
“…Thus, the results reported here suggest protective effects after DHT treatment on chronic EAE, proposing a therapeutic potential for this neuroactive steroid. Previous observations obtained in other experimental models of neurodegeneration described protective [40][41][42][43] or detrimental effects after DHT treatment [44,45] . Moreover, controversial results were also reported in models of MS [16][17][18]23] .…”
Section: Discussionmentioning
confidence: 72%
“…In addition, new experimental data, showing that a prolonged period of hypoestrogenicity disrupts both neuroprotective and anti-inflammatory actions of estradiol [11], may help to reconcile the results of animal studies with those of the WHIMS. Some clinical evidence also supports the potential cognitive benefit of testosterone therapy in men [8] and several experimental studies have identified neuroprotective actions of adrenal and testicular androgens [5,8]. However, it is clear that we need more basic information on the mechanisms involved in the neuroprotective actions of steroids to predict the conditions in which hormone treatments may have positive outcomes for brain function in humans and design the best possible therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Androgens exhibit a wide array of neuroprotective and neurotherapeutic effects in motoneurons [8]. Our previous studies have demonstrated that testosterone is neuroprotective following motoneuron loss.…”
mentioning
confidence: 99%
“…Androgens have robust neuroprotective effects on motoneurons, mediating a variety of cellular and molecular mechanisms [8]. Establishing which of these mechanisms, proteins, and pathways are involved in the androgen-mediated protection of motoneuron dendrites from injury-induced atrophy will be valuable contributions to establishing new neurotherapeutic strategies.…”
mentioning
confidence: 99%